Synthesis and Characterization of Silver Oxide and Silver Chloride Nanoparticles with High Thermal Stability - Rafiq H. Siddiqui, M.; Adil, S.F.; Assal, M.E.; Ali, Roushown; Al-Warthan, A. (Asian Journal of Chemistry, 2013)
In present studies, the synthesis of nanoparticles of silver oxide and silver chloride were carried out. The silver oxide nanoparticles were synthesized employing capping method while silver chloride nanoparticles were synthesized by simple precipitation of silver nitrate solution. Transmission Electron microscopic studies show that the size of silver oxide nanoparticles obtained is in the range of 2-10 nm while the size of silver chloride nanoparticles was found to be in the range of 2-12 nm. Silver chloride nanoparticles were found to be stable even at 650 ºC. Thermal studies suggest that silver chloride nanoparticles behave like ionic liquid or molten salt in the range of 455-650 ºC.